Laboratory testing of compressive and tensile strength on level ice and ridged ice from Svalbard region - Bonath, Victoria; Patil, Aniket; Fransson, Lennart; Sand, Björnar (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2013)
Compression and tensile strength properties are important input data for constitutive modelling. Still strength properties of ridged ice are not yet sufficiently investigated. During winter 2011 and 2012 field trips were performed to the Svalbard region with the aim to investigate structure and strength of pressure ridges. Core samples from different ridges and the surrounding level ice were taken and transported to the laboratory at Luleå University of Technology. Studies on thin sections of the ice samples under cross-polarized light delivered information about internal structure of the ice. Uniaxial compressive and tensile strength tests were performed with horizontal and vertical loading directions. The experimental procedure is explained in detail. Salinity and porosity were measured for each sample. In this paper the mechanical properties obtained from the testing are documented by consideration of crystal type, ice depth and total porosity. Godkänd; 2013; 20131201 (anipat)